2013
DOI: 10.1002/ca.22282
|View full text |Cite
|
Sign up to set email alerts
|

The posterior intercostal vein: A thermoregulatory gateway to the internal vertebral venous plexus

Abstract: The internal vertebral venous plexus (IVVP) plays a putative role in thermoregulation of the spinal cord. Cold cutaneous venous blood may cool, while warm venous blood from muscles and brown fat areas may warm the spinal cord. The regulating mechanisms for both cooling and warming are still unknown. Warm venous blood mainly enters the IVVP via the intervertebral veins. In the thoracic area these veins are connected to the posterior intercostal veins. In this study, anatomical structures were investigated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…Thus, the present specimens appeared to show a stage later than the “developmental delay” in the posterior part of the fetal internal plexus [ 13 ]. We found valves in the external veins, but smooth muscles in the internal veins were not identified although these structures were recently discussed in relation to thermoregulation of the adult spinal cord [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the present specimens appeared to show a stage later than the “developmental delay” in the posterior part of the fetal internal plexus [ 13 ]. We found valves in the external veins, but smooth muscles in the internal veins were not identified although these structures were recently discussed in relation to thermoregulation of the adult spinal cord [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 98%
“…The present observations do not appear to have been reported previously in the literature. According to Hoogland et al (2013), the vertebral venous system connects with the proximal part of the posterior intercostal veins via IVVs: they are considered to play an important role in heat transportation from the posterior intercostal veins to the vertebral venous system. Hoogland et al concluded that PIVs are essential anastomoses between the internal vertebral venous plexus and the AV.…”
Section: Discussionmentioning
confidence: 99%
“…The intervertebral veins (IVVs) connect the vertebral venous system with the azygos venous system indirectly via the PIVs. A complete valve is located at the proximal end of each PIV (Maros, 1981), which allows venous blood to drain into the vertebral venous system via the IVV (Hoogland et al, 2013). The main aims of this study were to examine the anatomical variations of the azygos venous system and compare the observations with existing classification systems, applying modifications as appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…P.V. Hoogland et al [13] указывают, что проксимальные части задних межреберных вен при их впадении в непарные вены имеют клапаны и гладкомышечные сфинктеры. Последние позволяют задним межреберным венам расширяться, превращая их в своеобразные камеры давления, и в тех сегментах, где в них впадают межпозвоночные вены, обусловливают ретроградный кровоток во внутренние позвоночные венозные сплетения.…”
unclassified
“…Так, в работе P.V. Hoogland et al [13] представлены фото гистологических препаратов, на которых в местах впадения межреберных вен в непарную вену демонстрируются клапаны в сочетании с гладкими мышечными сфинктерами, образующими утолщения стенок.…”
unclassified